Cryptocurrency Returns, Cybercrime and Stock Market Volatility: GAS and Regime Switching Approaches - Sanusi, Kazeem Abimbola; Dickason-Koekemoer, Zandri (International Journal of Economics and Financial Issues, 2022)
This study examines the behaviour of cryptocurrencies’ returns to stock market volatility and cybercrime in the South African economy. The study makes us Generalized Autoregressive Score Model (GAS) investigate the time-varying correlation between cryptocurrencies’ returns and cybercrime, and cryptocurrencies’ returns and stock market volatility by making use of daily time series data on different four types of Cryptocurrencies, Bitcoin, Ethereum, Tether and BNB from January 2019 to December 2021. The study also makes use of the regime-switching approach to regime-switching impacts on the cryptocurrencies’ returns. The empirical results obtained showed that cybercrime, on average, has negative impacts on the cryptocurrencies’ returns and the time-varying correlation between stock market volatility and each of the cryptocurrencies’ returns is largely positive. The stock market volatility impact is found to be regime-switching dependent. The study recommends that efforts to reduce cybercrime activities must be reinforced to deepen the use of digital currencies and policy measures must be taken to ensure reduced or moderate stock market volatility.